QOLP-24. PATIENTS'/PARENTS' EXPERIENCES OF RECEIVING OPTUNE DELIVERED TUMOR TREATMENT FIELDS: A PEDIATRIC BRAIN TUMOR CONSORTIUM STUDY: PBTC-048. (11th November 2019) - Lai, Jin-Shei; Goldman, Stewart; Hwang, Eugene; Kocak, Mehmet; Lulla, Rishi; Dhall, Girish; Robison, Nathan; Onar-Thomas, Arzu; Dunkel, Ira
Abstract: BACKGROUND: Optune-delivered TTFields is a promising anti-mitotic FDA-approved cancer therapy in adult patients with high-grade gliomas (HGG), although effectiveness is not yet proven in pediatric patients. A multicenter trial [NCT03033992] evaluating the feasibility and device-related toxicity for children with recurrent or progressive supratentorial high-grade glioma (HGG) and ependymoma is being conducted. This presentation reports the interim health-related quality of life (HRQOL) and device-use experiences reported by patients and parents. METHODS: Participating patients (aged 5–21 years) and one of their parents completed the following measures at baseline and prior to each intervention cycle: PROMIS Fatigue, Anger, Anxiety, Depressive Symptoms, Mobility, Upper Extremity Function, and Peer Relationships and Neuro-QOL Stigma. Participants completed an exit survey when they were off the study regarding their experiences wearing the device. RESULTS: This planned interim analysis included 11 patients (7 males/4 females) with supratentorial tumors: ten HGG and one ependymoma. Median age was 14.2 (6.4–21.3) years. Patients reported worse HRQOL than the norms on all domains. Of these 11 patients, 6 completed the exit survey. No significant changes (p< 0.05) between the baseline and the final assessment were found except for Stigma. Patients perceived less stigma at baseline than at the final assessment (t=2.82, p=0.0370). Of these 6 parents who completed the Exit Survey: most considered wearing the device to be easy (n=5).Patient reminders were unnecessary (n=5), patients rarely/didn't complain (n=4) or refuse (n=5) to wear the device, there was rare/no (n=4) difficulty with daily activities because of the device, and patients were not (n=4) or sometimes (n=2) embarrassed to wear the device. CONCLUSION: Preliminary results indicate Optune-delivered TTFields therapy is feasible and accepted by children and parent with no evidence of negatively impacting patients' QOL. Accrual has been expanded beyond the interim analysis.